2018
DOI: 10.3389/fnmol.2018.00034
|View full text |Cite
|
Sign up to set email alerts
|

Lpar2b Controls Lateral Line Tissue Size by Regulating Yap1 Activity in Zebrafish

Abstract: LPA signaling plays important roles during cell migration and proliferation in normal and pathological conditions. However, its role during sensory organ development remains unknown. Here we show a LPA receptor Lpar2b is expressed in the posterior lateral line primordium (pLLP) and mechanosensory organs called neuromasts (NMs) in zebrafish embryos. Lpar2b loss-of-function significantly reduces the number of NMs and hair cells in the posterior lateral line (pLL). Further analysis reveals that Lpar2b regulates t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…What’s more, some extracellular lipids or hormone signals can bond to G-protein-coupled receptors (GPCRs) and regulates Hippo-YAP signaling mediated by F-actin signaling ( Moya and Halder, 2019 ). Based on a series of researches on the crosstalk between lysophosphatidic acid (LPA) and Hippo-YAP signaling, it is suggested that LPA is an upstream signal of Hippo pathway, binding to GPCRs and regulating the activity of the downstream effector YAP, which further mediates gene expression and cell behaviors ( Yu et al, 2012 ; Moroishi et al, 2015 ; Park et al, 2016 ; Wang X. et al, 2018 ). In addition, Wnt signaling, cell polarity and metabolic property also enrich the transduction mechanism of Hippo-YAP signaling pathway ( Totaro et al, 2018b ; Xiang et al, 2018 ; Moya and Halder, 2019 ).…”
Section: Role Of Hippo-yap Signaling In Osteogenesis Angiogenesis Anmentioning
confidence: 99%
“…What’s more, some extracellular lipids or hormone signals can bond to G-protein-coupled receptors (GPCRs) and regulates Hippo-YAP signaling mediated by F-actin signaling ( Moya and Halder, 2019 ). Based on a series of researches on the crosstalk between lysophosphatidic acid (LPA) and Hippo-YAP signaling, it is suggested that LPA is an upstream signal of Hippo pathway, binding to GPCRs and regulating the activity of the downstream effector YAP, which further mediates gene expression and cell behaviors ( Yu et al, 2012 ; Moroishi et al, 2015 ; Park et al, 2016 ; Wang X. et al, 2018 ). In addition, Wnt signaling, cell polarity and metabolic property also enrich the transduction mechanism of Hippo-YAP signaling pathway ( Totaro et al, 2018b ; Xiang et al, 2018 ; Moya and Halder, 2019 ).…”
Section: Role Of Hippo-yap Signaling In Osteogenesis Angiogenesis Anmentioning
confidence: 99%